Radioprotective Effect of Growth Hormone (Somatotrophin) on Irradiated Long Bones of Young Albino Rats (Medical Forum Monthly, 2024)
Objective: To evaluate possible effects of Growth hormone in ameliorating the harmful effects of radiation on growing long bones of young albino rats.Study Design: Experimental studyPlace and Duration of Study: This study was carried out at Department of Anatomy, Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Centre (JPMC) Karachi from January 2009 to June 2009.Materials and Methods: 30 litters of 10 days of age of albino rats were taken for this study. They were divided into three groups: Group A (Control),Group B(Irradiated) was given 5Gy gamma radiation and Group C was given radiation and injection somatotrophin(Growth hormone). Each Group was further subdivided into two sub Groups according to their respective time period of treatment i-e., 2 and 4 weeks respectively. Their weight was observed weekly. Animals were sacrificed by etheranasthesia. Dissection was done and the long bones i,e., humerus and femur were taken out and their length and width measured by digital caliper.Results: A significant decrease in weight was noted and there was significant decrease in length and width of long bones in irradiated sub Groups B as compared to control Group A. There was significant increase in weight, length and width in long bones of irradiated and somatotrophin treated sub Groups of C as compared to irradiated sub Groups of B.Conclusion: Irradiation causes severe bone growth retardation. Growth hormone protects the bone injury and reverses the damage.